Optimizing Antitumor Necrosis Factor Treatment in Pediatric Inflammatory Bowel Disease With Therapeutic Drug Monitoring. Issue 1 (July 2020) - Pinto Pais, Isabel; Espinheira, Maria C.; Trindade, Eunice; Amil Dias, Jorge
Abstract : ABSTRACT: Biological agents have revolutionized inflammatory bowel disease treatment but primary nonresponse and secondary loss of response are common with resulting adverse outcomes. Clinical trials demonstrated an association between serum drug concentrations, as well as the presence of antidrug antibodies, and loss-of-response. Therapeutic drug monitoring (TDM), defined as the evaluation of drug concentrations and antidrug antibodies, is appearing as a strategy to optimize treatment and take full advantage from these drugs. TDM appears to be a promising tool in clinical practice, especially in pediatric patients, who have pronounced fluctuations in the pharmacokinetics of the drugs. The authors present a literature review about antitumor necrosis factor therapy optimization based on personalized treatment strategies according to TDM and possible strategies to recapture loss of response, including an algorithm for practical management.